Raksā rōk rai rat dūai kotmāi thabīan rāt : chabap-- ʻanēkprasong - Wīnat Sīsuk (Khrōngkān Khayāi ʻOngkhwāmrū čhāk Mǣ ʻĀi sū ʻAndāman phư̄a Kānčhatkān Panhā Sitthi nai Sathāna Bukkhon khō̜ng Khon Rai Rat Rai Sanchāt, 2009)
Legals aspects of people without nationality and minority groups in Thailand according to Thai laws and regulations.